Helicosina, a new genus of Neotropical Limosininae (Diptera: Sphaeroceridae) - Kuwahara, Gregory K.; Marshall, Stephen A.; Yau, Tiffany (Zootaxa, 2024)
The new genus Helicosina is described to include three new Neotropical species characterized by swollen hind femora, cruciate interfrontal setae, strongly flattened notum and a distinctly narrow-elongate surstylus. At least one species is associated with furled Heliconia leaves. The following new species are described: H. crena sp. nov. from Costa Rica, H. sica sp. nov. from Ecuador, and H. valga sp. nov. from Costa Rica and Panama.